1987
DOI: 10.1007/bf00849294
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional management of children with chronic renal failure

Abstract: Current information on the adaptations to progressive loss of renal function is presented. The assessment of renal function in infants and children using serum creatinine concentration and its derivatives is considered as are various methods for assessment of growth. Children with creatinine clearances less than 50% of normal, who do not have uremic symptoms (and who are not on dialysis), should be ingesting diets providing close to 100% of the RDA for calories with 8% of the calories as protein. Recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 133 publications
1
8
0
Order By: Relevance
“…In turn, while we do not feel that all pediatric patients receiving peritoneal dialysis should be evaluated for carnitine deficiency, we agree with a recent task force report that plasma carnitine levels should be obtained and that supplementation should be considered when symptoms such as severe muscle weak ness or cardiomyopathy arise in this setting [36].…”
Section: Discussionsupporting
confidence: 63%
“…In turn, while we do not feel that all pediatric patients receiving peritoneal dialysis should be evaluated for carnitine deficiency, we agree with a recent task force report that plasma carnitine levels should be obtained and that supplementation should be considered when symptoms such as severe muscle weak ness or cardiomyopathy arise in this setting [36].…”
Section: Discussionsupporting
confidence: 63%
“…However, the feed contributed less than the previously recommended 8% of energy derived from protein [18]. Although the percentage protein energy from the feed fell significantly in the 0 to 2-years group, this reflects an increasing energy intake rather than a decrease in protein intake.…”
Section: Discussionmentioning
confidence: 69%
“…Despite the unpalatable diets, most of the patients require a phosphate binder in order to counteract hyperphosphatemia. Calcium carbonate and calcium citrate bind the phosphate of the diet and serve as coadjutants in the supply of calcium requirements in the diet [134]. The recommended starting dose for calcium carbonate is 10–20 mg of elemental calcium per kilogram per day with subsequent increasing doses according to the observed levels of serum phosphate.…”
Section: Treatmentmentioning
confidence: 99%
“…However, discordant results in advanced renal failure have been presented by Uauy et al [133]who showed lack of any beneficial effects of a low-protein diet in ameliorating the progression of renal insufficiency. It is recommended that children with significant renal functional compromise should ingest a diet with 8% of calories derived from protein, 50–70% of this with a high biological value [128, 134]. High-calorie/low-protein supplements and low-protein foods like pasta and bread may be useful as adjunctive therapy [2].…”
Section: Treatmentmentioning
confidence: 99%